Evaluating the burden of caregivers of patients with visual impairment: a multicenter pilot study in Italian visual rehabilitation centers - Virgili, Gianni; Ferron, Francesco; Bartolomei, Federico; Van Nispen, Ruth; Costanzo, Eliana; Ciaffoni, Giovanni L.; Rellini, Emanuela; Turco, Simona; Piepoli, Marina; Di Pietro, Simona; Fortini, Stefania (Frontiers in Public Health, 2025)
IntroductionDespite growing evidence that underscores the importance of the caregiver’s role in the rehabilitation process, visual rehabilitation (VR) programs often overlook these needs. The aim of this pilot study is to investigate the caregiving burden (CB) among informal caregivers of visually impaired (VI) patients who attend Italian VR centers, setting the bases for large-scale research.MethodsFour Italian VR centers were involved. Demographic data and IADL (Instrumental Activities of Daily Living Scale) questionnaire to assess the degree of autonomy of VI patients were collected. Regarding the caregiver, the Italian validated version of the “Caregiver Burden Inventory (CBI)” was administered.ResultsFifty patients and their caregivers were included. The mean total CBI score was 23.6 points (SD 18.4), which is about the threshold for abnormal stress score. Moreover, 9 (18%) caregivers had scores ≥39, suggesting burn-out or mental disorder. The time-dependent (rho = 0.88), developmental (rho = 0.93), and physical burden (rho = 0.87) domains demonstrated the strongest correlations with overall CBI score. Furthermore, each additional hour of caring increased the score by 1.07 points (p = 0.004). No association was detected between total CBI score and other patient’s characteristics, including dual sensory deficit (auditory and visual), as well as patient’s IADL score.ConclusionIn this pilot study in VI patients attending VR services, about one half of caregivers of VI patients experienced stress, with 1 in 5–6 suffering from burn-out or mental health issues. Larger studies should assess both the outcome and the resources needed to screen for CB, with care integrated in the patient rehabilitation pathway.